Celluloid skyline New York and the movies - Sanders, James 1955- (New York Alfred A. Knopf, 2003)
Explores how movies have shaped, influenced, mythologized, and invented New York City in such films as "42nd Street," "Rear Window," "Taxi Driver," "Annie Hall," and "Ghostbusters," and reveals how the real-life New York City has been transformed by Hollywood.
Mythic Cities -- Sidewalk Moments -- Filming the City: 1896-1928 -- Dreaming the City -- New Yorkers in Hollywood -- Building the Dream -- The Studio Production System -- On the Town -- Emerald Cities -- Skylines of Fantasy -- Something Big -- Skyscraper and Office Building -- Street Scene -- Row House, Tenement, and Housing Project -- Domestic Elaborations -- Mansion, Apartment, and Loft -- Worlds of Difference -- Dead End and Rear Window -- Lofty Perches -- Penthouse, Terrace, Rooftop, and Nightclub -- Edge of the City -- Waterfront, Train Station, and Grand Hotel -- Dancing Lights -- Broadway and Times Square -- Eight Million Stories -- On Location -- Filming the City After 1945 -- Nighttown -- The Dark Side of the City -- Changing City -- Renewal and Preservation -- A Heightened Reality -- Street Meets Stage.
"A Borzoi book."
Includes bibliographical references (pages 460-464), filmography (pages 466-478) and index.
Keywords: New York (N.Y.) -- In motion pictures